Plygene inheritance of latex yield in hevea brasiliensi Muell. Arg. - Ohi Omokhafe, K.=700 1 Nasiru, I.
(En, Fr, Es)
ilus., 16 ref.
Keywords: HEVEA BRASILIENSIS; HEREDABILIDAD; HERENCIA GENETICA; RENDIMIENTO; LATEX; ITALIA; CAUCHO